A key role for NOX4 in epithelial cell death during development of lung fibrosis - Carnesecchi, Stephanie; Deffert, Christine; Donati, Yves; Basset, Olivier; Hinz, Boris; Preynat-Seauve, Olivier; Guichard, Cecile; Arbiser, Jack L; Banfi, Botond; Pache, Jean-Claude; Barazzone-Argiroffo, Constance; Krause, Karl-Heinz (Antioxidants & redox signaling, 2011)
The pathogenesis of pulmonary fibrosis is linked to oxidative stress, possibly generated by the reactive oxygen species (ROS) generating NADPH oxidase NOX4. Epithelial cell death is a crucial early step in the development of the disease, followed only later by the fibrotic stage. We demonstrate that in lungs of patients with idiopathic lung fibrosis, there is strong expression of NOX4 in hyperplastic alveolar type II cells. To study a possible causative role of NOX4 in the death of alveolar cells, we have generated NOX4-deficient mice. Three weeks after administration of bleomycin, wild-type (WT) mice developed massive fibrosis, whereas NOX4-deficient mice displayed almost normal lung histology, and only little Smad2 phosphorylation and accumulation of myofibroblasts. However, the protective effects of NOX4 deficiency preceded the fibrotic stage. Indeed, at day 7 after bleomycin, lungs of WT mice showed massive increase in epithelial cell apoptosis and inflammation. In NOX4-deficient mice, no increase in apoptosis was observed, whereas inflammation was comparable to WT. In vitro, NOX4-deficient primary alveolar epithelial cells exposed to transforming growth factor-β(1) did not generate ROS and were protected from apoptosis. Acute treatment with the NOX inhibitors also blunted transforming growth factor-β(1)-induced apoptosis. ROS generation by NOX4 is a key player in epithelial cell death leading to pulmonary fibrosis.